The poems of Elizabeth Siddal in context - Woolley, Anne (Book collections on Project MUSE., 2021)
Every Siddal poem is close read alongside works by Rossetti, Swinburne, Ruskin, Tennyson and Keats and with reference to prevailing cultural, political and religious contexts to give the most comprehensive analysis yet of this enigmatic, previously undervalued poetic voice.